An efficient fine granularity scalable coding scheme using adaptive leaky prediction - Yunlong Gao; Lap-Pui Chau (ICICS-PCM 2003 proceedings of the 2003 Joint Conference of the Fourth International Conference on Information, Communications & Signal Processing and Fourth Pacific-Rim Conference on Multimedia : 15-18 December 2003, Meritus Mandarin Singapore Hotel, Singa, 2003)
In this paper, we propose a novel method, which makes use of the advantages of bit-plane coding technique of fine granularity scalability (FGS) video coding scheme, and applies adaptive leaky factors for the enhancement layer prediction to further improve the coding efficiency. A flexible method that can dynamically determine the leaky factor values is also presented. Experimental results show that the proposed method can further improve the coding efficiency, and still keep the original characteristics, such as fine granularity, and bandwidth adaptation.